Case report: An ultrasound-based approach as an easy tool to evaluate hormone receptor-positive HER-2-negative breast cancer in advanced/metastatic settings: preliminary data of the Plus-ENDO study - Montella, Liliana; Di Marino, Luigi; Marino, Maria Adele; Riccio, Vittorio; Del Gaudio, Nunzio; Altucci, Lucia; Berretta, Massimiliano; Facchini, Gaetano (Frontiers in Oncology, 2024)
Background. Hormone receptor-positive tumors are unlikely to exhibit a complete pathological tumor response. The association of CDK 4/6 inhibitor plus hormone therapy has changed this perspective. Case Presentation In this study we retrospectively reviewed the charts of patients with a diagnosis of luminal A/B advanced/metastatic tumors treated with a CDK 4/6 inhibitor-based therapy. In this part of the study, we present clinical and ultrasound evaluation. Eight female patients were considered eligible for the study aims. Three complete and five partial responses were reported, including a clinical tumor response of 50% or more in 5 out of 9 assessed lesions (55%). All patients showed a response on ultrasound. The mean lesion size measured by ultrasound was 27,1±15,02 mm (range 6-47 mm) at the baseline; 16,08±14,6 mm (range 0-40 mm) after 4 months (T1) and 11,7±12,9 mm (range 0-30 mm) at the 6 months follow-up (T2). Two patients underwent surgery. The radiological complete response found confirmation in a pathological complete response, while the partial response matched a moderate residual disease. Conclusions The evaluation of breast cancer by ultrasound is basically informative of response and may be an easy and practical tool to monitor advanced tumors, especially in advanced/unfit patients who are reluctant to invasive exams.